Chemical gastritis induced by naproxen in the absence of Helicobacter pylori infection. Issue 1 (January 1995) - McCarthy, C J; McDermott, M; Hourihane, D; O'Morain, C
Abstract : AIM--To evaluate the histological changes that occur in the antral mucosa of healthy male subjects before and after one week of naproxen administration, using a chemical gastritis score according to the Helicobacter pylori status. METHODS--Nineteen male subjects (mean age 31 years) underwent two endoscopies: one before and the other after one week of naproxen treatment (1 g daily). Antral biopsy specimens were assessed for the presence of H pylori infection and for chemical gastritis, defined as the presence of foveolar hyperplasia, muscle fibres in the lamina propria, oedema, and vasodilatation, in the absence of acute or chronic inflammatory cell infiltrate. RESULTS--Of the 19 subjects, eight had H pylori infection. After one week of naproxen treatment, none of those with H pylori infection developed chemical gastritis, while five of 11 (45%) of those without H pylori infection did. In the absence of H pylori infection there was no evidence of inflammation, either before or after naproxen administration. CONCLUSIONS--A different pattern of antral histological change occurs following naproxen administration. This pattern is related to the presence or absence of H pylori infection, suggesting that H pylori status should be determined in histological studies of subjects taking non-steroidal anti-inflammatory drugs.